KEEFEKTIFAN TEKNIK AKROSTIK DALAM KETERAMPILAN MENULIS PUISI - SUMIYATI SUMIYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this study was to determine the effectiveness of the acrostic technique in learning poetry writing skills. Learning to write poetry is considered a difficult thing. Students tend to choose diction that is less precise, the courage of students to express ideas is still lacking and the acquisition of poetry writing results is still low and has not achieved minimal completeness. The research was carried out on conventional learning before the application of acrostic techniques and after the application of acrostic techniques in cycle I and cycle II. The research method used is Classroom Action Research which consists of planning, implementation, observation, and reflection. The subjects of this study were 38 students of class X SMK Negeri 1 Sindangbarang. Data collection techniques used are observation, and tests. Over all the data obtained were analyzed through the following stages: data reduction, data presentation, and conclusions. Based on the results of the research obtained, it can be concluded that the results of pre-action in writing poetry are still lacking. After the action was carried out with the application of acrostic techniques in improving learning to write poetry, it showed an increase in the moderate to good category. The results of this study indicate that the acrostic technique is effectively used in learning to write poetry and can improve students' competence in poetry writing skills. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui keefektifan teknik akrostik dalam pembelajaran keterampilan menulis puisi. Pembelajaran menulis puisi dianggap sebagai suatu yang sulit. Siswa cenderung memilih diksi yang kurang tepat, keberanian sis wa mengungkapkan ide masih kurang serta perolehan hasil menulis puisi yan maish rendah dan belum mencapai ketuntasan minimal. Penelitian dilaksanakan pada pembelajaran secara konvensional sebelum diterapkannya teknik akrostik dan setelah diterapkan teknik akrostik pada siklus I dan siklus II. Metode penelitian yang digunakan ialah Penelitian Tindakan Kelas yang terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah 38 siswa kelas X SMK Negeri 1 Sindangbarang. Teknik pengumpulan data yang digunakan adalah observasi, dan tes. Keseluran data yang diperoleh dianalisis melalui tahap-tahap: reduksi data, penyajian data, dan simpulan. Berdasarkan hasil penelitian yang diperoleh, dapat disimpulkan bahwa hasil pratindakan dalam menulis puisi tergolong masih kurang. Setelah tindakan dilakukan dengan penerapan teknik akrostik dalam meningkatkan pembelajaran menulis puisi menunjukkan adanya peningkatan sedang hingga berkategori baik. Hasil akhir penelitian ini menunjukan bahwa teknik akrostik efektif digunakan dalam pembelajaran menulis puisi serta dapat meningkatkan kompotensi siswa dalam keterampilan menulis puisi.